IMPLEMENTASI KEBIJAKAN PEDOMAN PENYULUH AGAMA NON PNS DALAM MENYATUKAN MEKANISME KERJA DAN PELAPORAN KINERJANYA - Dudung Abdul Rohman (Tatar Pasundan: Jurnal Diklat Keagamaan, 2018)
Religious extension agents have the main task of providing religious guidance and counseling to community communities who are the target group or fostered. Along with the development of religious and national issues, the Government, in this case the Ministry of Religion, considers the importance and strategic existence of this Religious Extension. So at the end of 2016 was selected and appointed thousands of Non PNS Religion Extension throughout Indonesia. In carrying out their duties and functions, they are still not uniform in terms of work mechanism and performance reporting. So the Ministry of Religion through the Director General of Islamic Guidance issued a policy in the form of Decree No. 298 of 2017 concerning Guidelines for Non Civil Servant Extension Workers. Through this policy there was a paradigm shift regarding the implementation of the duties and functions of Non PNS Religion Extension officers as well as the integration of work mechanisms and reporting on their performance. So that the performance of Non Civil Servant Religious Extension officers can be evaluated and accounted for accountability. So with this research can be seen concretely the implementation of the policy of Guidelines for Non Civil Servant Religion in integrating the work mechanism and performance reporting in the training activities at the Religious Training Center Bandung  Key words: Guidance, Implementation, Work Mechanism, Guidelines, Performance Reporting, Religious Counseling